Utilizing the dead-time effect to achieve decentralized reactive power sharing in islanded AC microgrids - Qi, Yang (2022)
In islanded ac microgrids, distributed energy storage systems (DESSs) are normally coupled to the grid through voltage source inverters (VSIs). To improve the operation efficiency and to avoid overloading, it is desirable that VSIs can share active and reactive powers in proportion to their respective power ratings. Although accurate active power sharing can be easily guaranteed by frequency droop control, it is difficult to achieve reactive power sharing as desired due to mismatched grid impedances and voltage sensor scaling errors. To overcome this challenge, a decentralized reactive power control scheme is proposed and used in conjunction with the conventional voltage droop control to enhance the reactive power sharing performance. Specifically, the proposed control scheme utilizes the dead-time effect to equalize the power factors of all VSIs. As a result, the reactive power sharing performance is improved in a fully decentralized manner. Finally, simulation and experimental results are provided to validate the effectiveness of the proposed control scheme.